Polemic with the review of the publication entitled Methodology as a way out. Research approaches and educational practices in andragogical studies on motherhood (Wrocław 2020) published by dr hab. Edyta Zierkiewicz in the journal Ars Educandi 18/2021. - Martyna Paulina Pryszmont (Studia z Teorii Wychowania)
The text is a polemic review of the publication entitled Methodology as a way out. Research approaches and educational practices in andragogical studies on motherhood (Wrocław 2020) published by dr hab. Edyta Zierkiewicz in the Ars Educandi magazine. The discussion is the result of a different methodological worldview of the author of the monograph and the author of the review. Nevertheless, the priority of this text is to express disagreement with the aggressive tone of the reviewer's statements, as well as the practices she uses to discredit the reviewed monograph.